Resiliensi Infrastuktur Dalam Mengelola Sarana Prasarana Di Lembaga Pendidikan - Abdulloh Muhamad Al-Kaff; Nadilla Aleyda Maqhfira Agustin; Sedya Santosa (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
This study aims to analyze strategies for managing educational facilities and infrastructure, as well as their resilience against disasters in educational institutions, to support sustainable education in the digital era and amid high-risk conditions. The method employed is a literature review with a qualitative approach, involving data collection from national/international journals, scientific articles, and books via platforms such as Google Scholar, PubMed, and DOAJ, followed by descriptive analysis to summarize findings and identify knowledge gaps. The results indicate that facility and infrastructure management encompasses seven main strategies planning, reception, inventory, security, storage, disposal, and evaluation while resilience against disasters involves five steps: disaster-resistant building design, utility backups, training simulations, recovery planning, and external collaborations. Integrating these strategies enhances resilience, minimizes disruptions, and ensures safety and continuity of the teaching-learning process.